Improving the age constraints on the archeological record in Scladina Cave (Belgium): new speleothem U–Th ages - H. B. Vonhof; S. Verheyden; D. Bonjean; S. Pirson; S. Pirson; M. Weber; D. Scholz; J. Hellstrom; H. Cheng; H. Cheng; X. Jia; K. Di Modica; et al. (Climate of the Past)
The sedimentary sequence in Scladina Cave (Belgium) is well-known for its rich Middle Paleolithic assemblages and its numerous faunal remains. Of particular interest is the presence of a nearly complete mandible of a Neanderthal child. To place all of these finds into the correct chronostratigraphic context, various dating techniques have been applied over the past decades. This resulted in a reasonably well-constrained age model, roughly spanning the last glacial cycle. Age constraints of the lower part of the Scladina sequence as well as from the underlying Sous-Saint-Paul Cave were, however, absent until now. Previous attempts to date several speleothem layers in Scladina Cave using U–Th dating were only partly successful, presumably because diagenetic alteration of speleothem material compromised the ages. In the present study we reassessed U–Th dating of various speleothem levels in Scladina Cave, applying state-of-the-art U–Th dating and carefully selecting material that experienced little to no diagenetic alteration. The new results constitute a robust age framework for the Scladina sequence, which provides precisely dated stratigraphic anchor points that improve the previous age model. Furthermore, new U–Th analyses for speleothems from the lower part of the Scladina sequence and from the Sous-Saint-Paul sequence document Middle Pleistocene ages, making this one of the longer fossil-rich cave sedimentary sequences in NW Europe. The new data confirm that speleothem growth predominantly took place in periods of warmer climate, while siliciclastic sediments characterize the colder intervals. New speleothem ages further suggest that the Neanderthal mandible found in the sequence and previously placed in Marine Isotope Stage 5a or 5b could potentially be as old as Marine Isotope Stage 5d.